Pengaruh Kepemilikan Manajerial, Ukuran Perusahaan dan Kompleksitas Perusahaan terhadap Audit Report Lag: Studi Empiris pada Perusahaan Sektor Pertambangan - Wahyu Septian R; Nelvirita Nelvirita (Universitas Negeri Padang, 2023)
This study aims to examine the effect of managerial ownership, firm size, and firm complexity on the audit report lag. The population in this study are all mining sector companies listed on the Indonesia Stock Exchange in 2018-2021. The sampling technique used was purposive sampling. The number of samples is 68 companies. The statistical method uses multiple linear regression analysis. The results show that managerial ownership has no effect on audit report lag, company size negatively affects audit report lag, company complexity does not affect audit report lag in mining sector companies listed on the Indonesia Stock Exchange in 2018-2021.